Divine fellowship in the Gospel of John: A Trinitarian spirituality - Van der Merwe, Dirk G. (HTS Teologiese Studies / Theological Studies, 2019)
This article investigates how Trinity features are presented in the Gospel of John and how the early Christians experienced the Trinity in their daily lives. The immanence and 'lived experiences' of the divine are fostered by how the immanence of the divine is expounded in terms of the familia Dei : God as Father, the Logos as Son of God, believers as Children of God and the Spirit-Paraclete as the one who constitutes the family and educates the children in the family. Therefore, in this article, the familia Dei will be the facilitating hermeneutical principle used to examine the divine fellowship as well as the 'lived experiences' and immanence of the divine in early Christian everyday living. John's reflection on perichoresis lies embedded in a 'fellowship' perspective. The divine fellowship is investigated from the four perspectives of how the divine is identified in John: life in the familia Dei , love in the familia Dei , unity in the familia Dei and glorification in the familia Dei.
free
Keywords: BIBLE. Gospels; CHRISTIAN spirituality; CHRISTIANS; DOCTRINAL theology; Divine-Fellowship; FELLOWSHIP; Familia Dei; Glorification; Identity; Life; Love; TRINITY; Trinity; Unity